Skutki wdrożenia zintegrowanego systemu zarządzania w przedsiębiorstwie przemysłu spożywczego (na przykładzie PWC "Odra" w Brzegu) - Szlachta, Krystyna (Results of Implementation of Integrated Management System in Food Industry Enterprise (on the Example of the Confectionery Company "Odra" in Brzeg), 2005)
The paper describes a process of implementation of an integrated management system in the company. Economic benefits of implemented systems are pointed out as well as its influence on company's credibility among customers and suppliers.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 2, s. 326-331